2021
DOI: 10.3390/ijms22147756
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ZnSO4, MnSO4 and FeSO4 on the Partial Hydrogenation of Benzene over Nano Ru-Based Catalysts

Abstract: Nano Ru-based catalysts, including monometallic Ru and Ru-Zn nanoparticles, were synthesized via a precipitation method. The prepared catalysts were evaluated on partial hydrogenation of benzene towards cyclohexene generation, during which the effect of reaction modifiers, i.e., ZnSO4, MnSO4, and FeSO4, was investigated. The fresh and the spent catalysts were thoroughly characterized by XRD, TEM, SEM, XPS, XRF, and DFT studies. It was found that Zn2+ or Fe2+ could be adsorbed on the surface of a monometallic R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Initially, 0.5 g Ru/TNSTs catalyst, 60 mL H 2 O, and 12 g ZnSO 4 •7H 2 O were introduced into the kettle. Among many possible additives [9,54,55], ZnSO 4 •7H 2 O is widely recognized as the best additive to enhance the selectivity of cyclohexene effectively [5,49]. Subsequently, 30 mL of benzene was added to the storage tank.…”
Section: Catalytic Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, 0.5 g Ru/TNSTs catalyst, 60 mL H 2 O, and 12 g ZnSO 4 •7H 2 O were introduced into the kettle. Among many possible additives [9,54,55], ZnSO 4 •7H 2 O is widely recognized as the best additive to enhance the selectivity of cyclohexene effectively [5,49]. Subsequently, 30 mL of benzene was added to the storage tank.…”
Section: Catalytic Testingmentioning
confidence: 99%
“…Such catalysts should be capable of modulating the relative rates of the two-step hydrogenation reactions, i.e., benzene to cyclohexene and cyclohexene to cyclohexane [6][7][8], thereby yielding more cyclohexene product. Currently, non-loaded RuZn catalysts are widely used in industry [9,10], but they have drawbacks, including containing a high amount of precious metal Ru, typically greater than 80% by weight, and poor catalyst stability. Additionally, the zirconia additive, used to prevent the agglomeration of RuZn, is challenging to control the dispersion.…”
Section: Introductionmentioning
confidence: 99%
“…In the seventh article (research) [7], Yuan-Chang Liang et al reported the development of a brush-like Fe 2 O 3 -ZnO nanostructures towards NO 2 gas sensing based on the control of appropriate material synergistic effects. Further, Zhikun Peng et al [8] reported the influence of ZnSO 4 , MnSO 4 and FeSO 4 on the partial hydrogenation of benzene over nano Ru-Based catalysts. The ninth published research article by Xiaoyu Yu et al [9], discussed the development of an optimized synthesis approach for ZnO quantum dots (QDs) modified with polyvinylpyrrolidone (PVP40) which can potentially be applied in the fields of photoluminescence and photodynamic tumor suppression.…”
mentioning
confidence: 99%